Characteristics and Academic Productivity Among Pediatric Plastic Surgeons in the United States. (October 2021) - Egro, Francesco M.; Williams, Abraham A.; Roy, Eva; Smith, Brandon T.; Goldstein, Jesse A.; Losee, Joseph E.; Nguyen, Vu T.
Background: The characteristics that predispose plastic surgeons to a career in pediatric plastic surgery remain unclear. Therefore, the aim of this study is to analyze the characteristics of current pediatric plastic surgeons and to determine their academic productivity. Methods: Pediatric plastic surgeons were identified through an internet search of all academic children's hospitals affiliated with an Accreditation Council for Graduate Medical Education–accredited integrated or independent plastic surgery program. Demographics, training background, institutional and leadership positions, and academic productivity were determined. Results: A total of 304 pediatric plastic surgeons were identified. The majority of pediatric plastic surgeons were white (n = 217, 71.8%) males (n = 235, 77.6%). Clinical fellowships were completed by 86.8% (n = 263) of the cohort, with craniofacial (n = 181, 59.7%) being the most common followed by hand (n = 54, 17.8%); 41.1% had clinical fellowship training at 10 institutions, with the top 3 most represented programs being University of Pennsylvania (n = 19, 6.2%), University of California-Los Angeles (n = 16, 5.3%), and Harvard University (n = 15, 4.9%); 25.7% (n = 78) held leadership positions within their institutions. A significant higher academic productivity was found among research fellowship-trained surgeons, chiefs of pediatric plastic surgery, fellowship directors, and members of departments of plastic surgery. Those who completed an independent residency had a significant higher H-index and number of citations. Conclusion: Pediatric plastic surgery is represented by surgeons of diverse training background. An elite cohort of programs has trained the most pediatric plastic surgeons. Lastly, high academic productivity was found to be correlated with certain demographic and leadership variables highlighting its impact on career advancement.